Efficacy of sacral nerve modulation evaluated with International Consultation on Incontinence Questionnaire-Bowels. A prospective case series assessing efficacy one month after implantation of a sacral nerve modulator - Kvalvik, Julia Christina Joanis (UiT Norges arktiske universitet, 2019)
Objective: Sacral nerve modulation (SNM) is an established method for treating faecal incontinence (FI) if conservative measures fail. The International Consultation on Incontinence Questionnaire-Bowels (ICIQ-B) is a patient-completed symptom and quality of life assessment tool created by clinical experts with patient input. The purpose of this study was to use the ICIQ-B to evaluate the short-term efficacy of SNM in patients with FI. Method: This was a prospective case series involving all patients with FI eligible for SNM at the University Hospital of Northern Norway (UNN). Patients were scored with ICIQ-B and St. Mark’s score at baseline and one month after SNM. Primary endpoint was efficacy defined as a change in ICIQ-B score from baseline to one month after SNM. Secondary outcomes were change in St. Mark’s score and the assessment of non-responders, defined as no change in score or higher score at one month, comparing the ICIQ-B to the St. Mark’s score. Results: All 17 patients that were treated with SNM between February 2018 and October 2018 were included in this study. All domains in the ICIQ-B showed a significant change in score from baseline to one month after SNM, except the domain concerning sexual impact. The bowel pattern score (0-21) had a mean change of 2.7 (95% CI: 1.2 - 4.2, p = 0.002), whereas the bowel control score (0-28) had a change of 6.8 (95% CI: 5.9 - 8.6, P < 0.001). A mean change of 1.7 (95% CI: 0.84 - 2.57, p = 0.001) was seen in the other bowel symptoms score (0-15). The quality of life score (0-26) showed a mean difference of 8.1 (95% CI: 4.5 - 11.7, p < 0.001), and the overall quality of life score (0-10) presented a change of 2.7 (95% CI: 1.3 - 4.1, p = 0.001). The St. Mark’s score (0-24) had a mean change in score of 4.5 (95% CI: 3.0 - 5.9, p < 0.001). Seven patients (41%) were non-responders with the ICIQ-B compared to one (6%) in the St. Mark’s group. Conclusion: A significant reduction in score one month after treatment with SNM was seen in 5/6 domains of the ICIQ-B ...